Creating Trust by a Leader - Dorota Balcerzyk; Dariusz Karczewski (Communications of International Proceedings, 2021)
The article addresses the trust of a leader in modern reality based on literature review and own research. In the publication, a critical analysis of the trust literature was performed. The specificity of the role and expectations towards the leader in an organization is presented. The research results concerning the creation of trust by a leader allow pointing out several significant factors. In creating trust in relations with subordinates, leaders rely on using team members' ideas and solutions and delegating authority, with complete trust towards their success. An important factor in creating trust is the conviction that subordinates are succeeding rather than failing. Moreover, leaders are willing to accept responsibility for their subordinates' failures, and they believe that actions taken by them to create trust aim at improving team leadership. The presented considerations concluded that creating trust in the leader-subordinate relationship in the organization is heading in a positive direction. Trust creation in a new, complex, and changing environment can be the basis for achieving goals and missions despite difficulties and uncertainties.
Keywords: Trust; Leadership; Leader; Manager; Team Management